Positive electrode and secondary battery

By designing a coating containing the first positive electrode active material and inorganic filler in the positive electrode sheet, the number of particle stacking layers and particle size are controlled, thus solving the thermal runaway problem of secondary batteries under abuse conditions and achieving a balance between safety and electrochemical performance.

CN117673245BActive Publication Date: 2025-01-14BYD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211047596.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-29
Publication Date
2025-01-14
Estimated Expiration
2042-08-29

AI Technical Summary

Technical Problem

Secondary batteries are prone to thermal runaway when abused due to contact between the positive electrode current collector and the negative electrode active material layer. Existing technologies are difficult to effectively prevent such short circuit modes, and may affect the battery's internal resistance and electrochemical performance.

Method used

Design a positive electrode sheet including a first positive electrode coating and a second positive electrode coating. The first coating contains a first positive electrode active material and an inorganic filler with no electrochemical activity. By controlling the number of particle stacking layers n in the range of 4-7, combined with appropriate particle size and thickness, it ensures protection of the positive electrode current collector under abuse conditions, reduces the risk of short circuit, and conducts Joule heat through the thermal conductivity of the inorganic filler.

Benefits of technology

It effectively prevents thermal runaway of the battery under abuse conditions, reduces the increase in internal resistance, maintains the battery's safety and electrochemical performance, and ensures the battery's energy density and cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117673245B_ABST
    Figure CN117673245B_ABST
Patent Text Reader

Abstract

The present application provides a positive electrode plate and a secondary battery. The positive electrode plate includes a positive electrode current collector and a first positive electrode coating and a second positive electrode coating sequentially stacked on the positive electrode current collector; the number of particle stacking layers in the first positive electrode coating is defined as n=T x (M + 1) / (M x D 1 v 50+D 2 v 50), and n is in the range of 4-7; wherein T is the thickness of the first positive electrode coating, in μm; M is the mass ratio of the first positive electrode active material to the inorganic filler contained in the first positive electrode coating, D 1 v 50. D 2 v 50 is the particle size value corresponding to the cumulative volume distribution percentage of the first positive electrode active material and the inorganic filler reaching 50%, D 1 v 50 is 0.6-1.2μm, D 2 v 50 is 0.6-1.5μm. The particle accumulation in the first positive electrode coating is appropriate, and the internal resistance of the battery can be controlled within a small range while ensuring the safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet and a secondary battery. Background Art

[0002] Secondary batteries have been widely used in consumer electronics (such as mobile phones, tablets) and electric vehicles. However, secondary batteries are prone to short circuits in the battery under conditions of abuse such as puncture, extrusion, and collision, releasing a large amount of Joule heat, which in turn causes thermal runaway. Among the several common short circuit modes inside the battery, the short circuit caused by the contact between the positive electrode collector (such as aluminum foil) and the negative electrode active material layer releases the most heat and is the most dangerous short circuit mode of the battery. Therefore, it is necessary to provide effective safety measures for this short circuit mode. Summary of the invention

[0003] In view of this, the embodiments of the present application provide a positive electrode plate and a secondary battery, which can effectively solve the thermal runaway problem caused by the positive current collector of the battery contacting the negative electrode, while also controlling the internal resistance increase of the battery within a smaller range to avoid affecting the electrochemical performance of the battery under normal operation.

[0004] In a first aspect, the present application provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a first positive electrode coating and a second positive electrode coating sequentially stacked on at least one side surface of the positive electrode current collector; the first positive electrode coating comprises a first positive electrode active material and an inorganic filler without electrochemical activity, and the second positive electrode coating comprises a second positive electrode active material; the number of particle stacking layers n in the first positive electrode coating is defined to satisfy the following relationship:

[0005] n=T×(M+1) / (M×D 1 v 50+D 2 v 50), and n is in the range of 4-7;

[0006] Wherein, T is the thickness of the first positive electrode coating, in μm; M is the mass ratio of the first positive electrode active material to the inorganic filler, D 1 v 50. D 2 v 50 are the particle sizes corresponding to the volume cumulative distribution percentages of the first positive electrode active material and the filler when they reach 50%, both in μm; wherein, D 1 v 50In the range of 0.6-1.2μm, the D 2 v 50 in the range of 0.6-1.5μm.

[0007] In the positive electrode plate provided in the first aspect of the present application, by establishing a relationship between the thickness of the first positive electrode coating and the mass ratio of the first positive electrode active material and the inorganic filler contained therein and the median particle size of the two particles, a relationship formula for the number of particle stacking layers n of the first positive electrode coating is defined, and n is controlled within the range of 4-7, and at the same time, the median particle sizes of the first positive electrode active material and the inorganic filler are respectively 0.6μm-1.2μm and 0.6μm-1.5μm, so that the number of stacking layers and density of the particles in the first positive electrode coating can be ensured to be appropriate, and the positive electrode collector can be effectively protected in the event of abuse such as puncture and extrusion of the battery, thereby preventing the positive electrode collector from contacting the negative electrode to cause thermal runaway, and the internal resistance of the battery will not be too large under normal operation to affect the electrochemical performance.

[0008] In a second aspect, the present application provides a secondary battery, the secondary battery comprising the positive electrode sheet as described in the first aspect of the present application. The secondary battery has low internal resistance and good safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1A A schematic diagram of the structure of the negative electrode plate provided in an embodiment of the present application.

[0010] Figure 1B Another schematic diagram of the structure of the negative electrode plate provided in an embodiment of the present application. DETAILED DESCRIPTION

[0011] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.

[0012] Please also read Figure 1A and Figure 1B The embodiment of the present application provides a positive electrode plate 10, which includes a positive electrode current collector 11 and a first positive electrode coating 12 and a second positive electrode coating 13 sequentially stacked on at least one side of the positive electrode current collector 11; the first positive electrode coating 12 includes a first positive electrode active material and an inorganic filler without electrochemical activity, and the second positive electrode coating 13 includes a second positive electrode active material; the number of particle stacking layers n in the first positive electrode coating 12 is defined to satisfy the following relationship:

[0013] n=T×(M+1) / (M×D 1 v 50+D 2 v 50), and n is in the range of 4-7;

[0014] Wherein, T is the thickness of the first positive electrode coating 12, in μm; M is the mass ratio of the first positive electrode active material to the inorganic filler, D 1 v 50. D 2v 50 are the particle sizes corresponding to the volume cumulative distribution percentages of the first positive electrode active material and the filler when they reach 50%, both in μm; wherein, D 1 v 50In the range of 0.6-1.2μm, the D 2 v 50 in the range of 0.6-1.5μm.

[0015] In the above-mentioned positive electrode sheet, two positive electrode coatings are arranged on one side of the positive electrode collector 11 at the same time, and the first positive electrode coating 12 close to the positive electrode collector 11 is controlled to contain the first positive electrode active material and the inorganic filler at the same time. The first positive electrode coating 12 can play a safety protection role. With the help of the high thermal stability and non-conductivity of the inorganic filler, the contact opportunity between the positive electrode collector 11 and the negative electrode active material layer can be reduced when the battery is squeezed, collided, punctured, etc., thereby reducing the probability of short circuit in the battery; and in the initial stage of the internal short circuit of the battery, the inorganic filler with good thermal conductivity can also conduct the Joule heat generated by the short circuit as soon as possible, reduce the heat concentration and the continuous increase of the battery core temperature, and improve the battery safety; in addition, the presence of the inorganic filler also reduces the distribution sites of the active material in the first positive electrode coating, reduces the risk of oxidative decomposition of the electrolyte, and reduces the heat generated by the decomposition reaction. The first positive electrode active material can participate in the charging and discharging process of the battery under normal conditions, contribute capacity, and reduce the loss of battery core energy density and the increase of internal resistance caused by the safety coating (such as the filler layer) without electrochemical activity.

[0016] The applicant found that the stacking layer number and stacking density of the first positive electrode active material particles and the inorganic filler particles in the first positive electrode coating 12 have a great influence on the safety and internal resistance of the battery, and the industry rarely pays attention to this. The applicant defines a quantitative relationship between the number of particle stacking layers n in the first positive electrode coating 12 by establishing a relationship between the thickness T of the first positive electrode coating 12, the mass ratio M of the first positive electrode active material particles and the inorganic filler particles, and the median particle size (i.e., Dv50) of the two particles, and controls n to be within the range of 4-7, the median particle size of the first positive electrode active material to be 0.6μm-1.2μm, and the median particle size of the inorganic filler to be 0.6μm-1.5μm, so that the number of stacking layers and density of the particles in the first positive electrode coating can be ensured to be appropriate, which can effectively protect the positive electrode current collector 11, while not sacrificing too much energy density of the battery, and not increasing the value of the battery internal resistance too much to affect the battery's electrochemical performance such as cycle.

[0017] Specifically, when the above n is less than 4, the number of stacking layers of particles in the first positive electrode coating 12 is too low and the particles are too loosely stacked, which will result in the first positive electrode coating 12 not being able to adequately protect the positive electrode current collector 11 when the battery is squeezed, collided, or punctured, and this may easily cause direct contact between the positive electrode current collector 11 and the negative electrode active material layer, and the safety of the battery cannot be guaranteed. When n is greater than 7, the number of stacking layers of particles in the first positive electrode coating 12 is too high and the particles are too densely stacked, which will increase the internal resistance of the battery cell too much, making it difficult for the electrolyte to penetrate the first positive electrode coating 12, and affecting the battery's cycle performance. In addition, the median particle size of the first positive electrode active material particles and the inorganic filler particles is not much different, which can ensure that the stacking of the two particles after mixing will not be too dense.

[0018] Among them, D of the first positive electrode active material particles 1 v 50 may be 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, etc.; in some embodiments, D 1 v 50 is in the range of 0.6μm-0.9μm. D of inorganic filler 2 v 50 can be 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, etc.

[0019] In this application, the above D 1 v The specific value of 50 can be obtained from the particle size distribution diagram of the first positive electrode active material obtained by laser diffraction method. The test method can be found in GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method. The test instrument is generally a laser particle size analyzer (such as Malvern 3000 laser particle size analyzer). Similarly, the above D 2 v 50 can be obtained from the particle size distribution diagram of inorganic fillers obtained by laser diffraction method. Among them, the particle size D corresponding to the volume cumulative distribution percentage of a certain material particle reaches 50% v 50 can also be referred to as the “median particle size” of the material. In addition, the above T can be obtained by directly or indirectly measuring the thickness of the first positive electrode coating 12. The above M can be obtained by analyzing the composition of the first positive electrode coating 12.

[0020] It should be noted that in the present application, the positive electrode current collector 11 may have a laminated structure having a first positive electrode coating 12 and a second positive electrode coating 13 on one side of the surface (eg Figure 1AAs shown), it can also be a stacked structure with a first positive electrode coating 12 and a second positive electrode coating 13 on both sides of the positive electrode current collector 11 (as shown Figure 1B As shown). When both sides of the positive current collector 11 have the above-mentioned stacked structure, it is sufficient as long as the first positive electrode coating of the stacked structure on any one side satisfies the parameter n in the range of 4-7. Of course, it is also possible that the first positive electrode coating in the stacked structure on both sides of the positive current collector satisfies the parameter n in the range of 4-7. Among them, the positive current collector 11 may include aluminum foil, aluminum alloy foil, aluminum-plated organic film, carbon-coated aluminum foil, carbon-coated aluminum alloy foil, or carbon-coated aluminum-plated organic film. In some embodiments, the positive current collector 11 is aluminum foil or aluminum alloy foil.

[0021] In the embodiment of the present application, the mass ratio M of the first positive electrode active material to the inorganic filler can be in the range of 1 to 5. M in this range helps to ensure that the first positive electrode coating 12 plays a due safety protection role, while not making the mass ratio of the inorganic filler without electrochemical activity too high to affect the energy density of the battery.

[0022] To ensure that the first positive electrode coating 12 has better safety performance, in the embodiment of the present application, the thickness T of the first positive electrode coating 12 can be controlled in the range of 2μm-10μm. The thickness T here refers to the thickness of a single-layer first positive electrode coating. In some embodiments, the thickness T of the first positive electrode coating 12 can be in the range of 4μm-7μm. At this time, the thickness of the first positive electrode coating 12 is appropriate, which not only has an effective safety protection effect, but also does not increase the amount of binder due to its excessive thickness and reduce the capacity contribution of the first active material.

[0023] In the embodiment of the present application, the thermal decomposition temperature of the inorganic filler is greater than or equal to 300°C. The inorganic filler has good thermal stability and will not fail before the battery thermal runaway, ensuring that the first positive electrode coating 12 can effectively play a safety function. In some embodiments, the inorganic filler may include one or more of boehmite, alumina, zirconium oxide, silicon dioxide, magnesium hydroxide, etc. Among them, the thermal decomposition starting temperature of boehmite is about 350°C; the thermal decomposition starting temperature of magnesium hydroxide is about 340°C.

[0024] In some embodiments, the inorganic filler is boehmite. Boehmite has good thermal conductivity and low hardness, and can conduct the Joule heat generated by the short circuit inside the battery cell as quickly as possible to reduce heat concentration. At the same time, since the Mohs hardness of boehmite is less than 5, its low hardness makes the coating equipment less damaged when coating the slurry for preparing the first positive electrode coating 12, and ensures that the film layer of the first positive electrode coating 12 is flat, which is conducive to the attachment of the second positive electrode coating 13 thereon, and ensures a high product yield in mass production.

[0025] In the present application, the first positive electrode coating 12 may further include a first binder and a first conductive agent, and the second positive electrode coating 13 may further include a second binder and a second conductive agent. The presence of a binder and a conductive agent in the two positive electrode coatings may ensure good adhesion and conductivity of each coating. The first binder, the second binder, the first conductive agent, and the second conductive agent may be conventionally selected in the field of batteries. Wherein, the first binder and the second binder are independently selected from polyvinylidene fluoride (PVDF), a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of vinylidene fluoride-acrylic acid, polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyacrylates (such as polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, etc.), polyvinyl alcohol (PVA), polyimide (PI), polyurethane, epoxy resin, styrene-butadiene rubber (SBR), fluorinated rubber, sodium carboxymethyl cellulose (CMC-Na), etc. One or more. The first conductive agent and the second conductive agent are independently selected from one or more of conductive carbon black (such as acetylene black, Ketjen black, Super P, 350G carbon black, etc.), graphite, carbon fiber, carbon nanotubes, graphene, etc., but are not limited thereto.

[0026] In the embodiment of the present application, the mass proportion of the first binder in the first positive electrode coating 12 is greater than the mass proportion of the second binder in the second positive electrode coating 13. The content of the binder in the first positive electrode coating 12 is higher than that in the second positive electrode coating 13, which ensures that the adhesion between the first positive electrode coating 12 and the positive electrode current collector 11 is strong. In the case of abuse such as extrusion, collision, puncture, etc. of the battery, even if the second positive electrode coating 13 falls off, the first positive electrode coating 12 will not fall off from the surface of the positive electrode current collector 11, avoiding contact between the positive electrode current collector 11 and the negative electrode active material layer, increasing the short-circuit resistance, reducing the risk of thermal runaway of the battery cell, and better improving the safety performance of the battery.

[0027] In addition, when the mass proportion of the binder in the first positive electrode coating 12 is high, if the mass proportion of the first positive electrode active material in the first positive electrode coating 12 is the same as the mass proportion of the second positive electrode active material in the second positive electrode coating 13, the mass proportion of the first conductive agent in the first positive electrode coating 12 is lower than the mass proportion of the second conductive agent in the second positive electrode coating 13. In this way, the first positive electrode coating 12 with slightly poor conductivity can better wrap and passivate the positive electrode current collector 11 under battery abuse conditions, reducing its contact with the negative electrode plate of the battery.

[0028] In the embodiment of the present application, the mass proportion of the first binder in the first positive electrode coating 12 is 5%-10%, for example, 5%, 6%, 7%, 8%, 9% or 9.5%, etc. This mass proportion of the first binder can avoid that the amount of the first binder is too small to provide a good bonding effect, making the first positive electrode coating 12 easy to fall off, and can also avoid that the amount of the first binder is too large to reduce the content of the first positive electrode active material in the first positive electrode coating 12, and lose the energy density of the battery.

[0029] In the embodiment of the present application, the mass proportion of the first conductive agent in the first positive electrode coating 12 is 1-3%. This is conducive to ensuring that the conductivity of the first positive electrode coating 12 is appropriate, and the content of the first conductive agent will not be too low, which will cause the internal resistance of the battery to be too high and deteriorate the low temperature, rate, and cycle performance of the battery, and the content of the first conductive agent will not be too high, which will reduce the short-circuit internal resistance and reduce the safety of the battery.

[0030] In some embodiments of the present application, the first positive electrode coating 12 may include the following components in percentage by weight: 50-85% of a first positive electrode active material, 10-40% of an inorganic filler, 5-10% of a first binder, and 1%-3% of a first conductive agent.

[0031] The second positive electrode coating 13 in the present application is equivalent to the positive electrode active material layer of a conventional non-safety battery, in which no safety coating is provided between the layer and the positive electrode current collector 11. Therefore, the second positive electrode coating 13 is a conventional component in the battery field, and it mainly plays the role of contributing energy.

[0032] In some embodiments of the present application, the second positive electrode coating 13 may include the following components in percentage by weight: 90-99% of the second positive electrode active material, 0.5-1.5% of the second binder, and 0.5-1.5% of the second conductive agent.

[0033] In the present application, the first positive electrode active material and the second positive electrode active material may be the same or different materials, and may be independently selected from one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium vanadium fluorophosphate, lithium cobaltate, lithium manganate, lithium nickelate, lithium vanadate, lithium titanate, lithium nickel manganate, lithium nickel cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based materials, etc. These positive electrode active materials may be undoped or modified by doping, and the surface may have a coating layer or not. Generally, phosphate active materials usually have a coating layer.

[0034] In order to ensure the good safety of the battery, in the embodiment of the present application, the structural stability of the first positive electrode active material is higher than the structural stability of the second positive electrode active material. At this time, the first positive electrode active material and the second positive electrode active material are materials of different materials. In some embodiments, the above-mentioned first positive electrode active material is a phosphate active material, and the second active material is a layered transition metal oxide. Specifically, the first positive electrode active material may include one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, and lithium vanadium fluorophosphate. The second active material may include one or more of lithium cobaltate, lithium manganate, lithium nickelate, lithium vanadate, lithium titanate, lithium nickel manganate, lithium nickel cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum, lithium-rich manganese-based materials, etc. In some embodiments, the second positive electrode active material is lithium cobaltate with a higher operating voltage and a higher specific capacity.

[0035] In the embodiment of the present application, the median particle size of the second positive electrode active material (which can be recorded as D 3 v 50) is in the range of 6 μm-18 μm. At this time, the median particle size of the second positive electrode active material is relatively large, its specific surface area is not too large, and its structural stability is relatively high. At the same time, the conduction of lithium ions will not be slowed down and the contact between the particles and the current collector will not be deteriorated due to the excessive particle size. In some embodiments, the median particle size of the second positive electrode active material is in the range of 14-16 μm.

[0036] The above-mentioned positive electrode plate 10 can be prepared by the following method: a first positive electrode slurry containing a first positive electrode active material, an inorganic filler, a first binder and a first conductive agent is sequentially layered on at least one side surface of a positive electrode collector 11 to form a first positive electrode coating 12 by drying, and a second positive electrode slurry containing a second positive electrode active material, a second binder and a second conductive agent is dried to form a second positive electrode coating 13 by drying, and after pressing, a positive electrode plate is obtained.

[0037] The positive electrode current collector may be coated on one side or on both sides. In other words, a laminated structure of a first positive electrode coating and a second positive electrode coating may be formed on one side of the positive electrode current collector, or a laminated structure of a first positive electrode coating and a second positive electrode coating may be formed on both sides of the positive electrode current collector. When the negative electrode current collector is coated on both sides, it is sufficient as long as the first positive electrode coating on any one side satisfies the defined parameter n in the aforementioned range.

[0038] The embodiment of the present application further provides a secondary battery, which includes the positive electrode sheet 10. Since the secondary battery includes the positive electrode sheet 10, the secondary battery has good safety performance and high energy density.

[0039] The secondary battery may be a liquid battery using a liquid electrolyte, or a semi-solid or solid battery using a semi-solid electrolyte or a solid electrolyte. The secondary battery may be a lithium secondary battery, a sodium secondary battery, a potassium secondary battery, a magnesium secondary battery, an aluminum secondary battery, a zinc secondary battery, etc.

[0040] In some embodiments, the secondary battery may include the above-mentioned positive electrode sheet, negative electrode sheet, and a semi-solid electrolyte or solid electrolyte disposed between the positive electrode sheet and the negative electrode sheet. In addition, when a semi-solid electrolyte or solid electrolyte is used, the positive electrode sheet and the negative electrode sheet may also contain a semi-solid electrolyte material or a solid electrolyte material.

[0041] In some other embodiments, the secondary battery may include the above-mentioned positive electrode sheet, negative electrode sheet, and a separator and electrolyte disposed between the positive electrode sheet and the negative electrode sheet. The secondary battery may be assembled by the following method: stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence to form a battery cell; placing the battery cell in a battery housing, injecting electrolyte, and then sealing the battery housing to obtain a secondary battery.

[0042] Among them, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector. Specifically, the negative electrode current collector may include but is not limited to copper foil, copper alloy foil, carbon-coated copper foil or copper-plated film, etc. The negative electrode active material in the negative electrode active material layer includes but is not limited to one or more of carbon materials, silicon-based materials, tin-based materials, and lithium titanate. Among them, the carbon material includes one or more of soft carbon, hard carbon, carbon fiber, graphitized carbon microspheres, artificial graphite, and natural graphite. Silicon-based materials may include one or more of elemental silicon, silicon alloys, silicon oxides, silicon-carbon composite materials, etc. Tin-based materials may include one or more of elemental tin, tin oxides, tin-based alloys, tin-carbon compounds, etc.

[0043] The diaphragm is usually a porous substrate for active ions to shuttle back and forth, and the diaphragm can be a one-layer or multi-layer structure. Exemplarily, the diaphragm can include but is not limited to a single-layer PP (polypropylene) film, a single-layer PE (polyethylene) film, a double-layer film PP / PE, a double-layer film PP / PP and a three-layer PP / PE / PP polymer diaphragm, or a non-woven fabric, etc. Among them, the electrolyte generally includes an electrolyte salt containing active ions (such as a lithium salt), a solvent (such as an organic solvent) and optional additives, etc. Among them, the organic solvent can include but is not limited to one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, propyl propionate, ethyl propionate, ethyl acetate, etc.

[0044] The present application also provides an electric device, which is provided with the secondary battery of the present application. The electric device may be a means of transportation, such as a car (such as an electric car), a ship, etc., or a 3C product (such as a mobile phone, a tablet computer, a smart bracelet), etc.

[0045] The technical solution of the present application is further described below in conjunction with a number of specific embodiments.

[0046] Example 1

[0047] A preparation method of a positive electrode sheet comprises the following steps:

[0048] (1) The first positive electrode active material (specifically lithium iron phosphate, as shown in Table 1, with a median particle size D 1 v 50 is 0.8 μm), inorganic filler (specifically boehmite, median particle size D 2 v 50 is 0.8 μm, the thermal decomposition starting temperature is 350° C.), a binder (specifically PVDF), and a conductive agent (specifically conductive carbon black) are mixed in an NMP solvent in a mass ratio of 57:30:10:3 (the aforementioned parameter M=1.9), and stirred evenly to obtain a first positive electrode slurry;

[0049] The second positive electrode active material (specifically lithium cobalt oxide, with a median particle size of 16 μm), a binder (specifically PVDF), and a conductive agent (specifically conductive carbon black) are mixed in an NMP solvent at a mass ratio of 98:1:1, and stirred evenly to obtain a second positive electrode slurry;

[0050] (2) The first positive electrode slurry is coated on one side of the aluminum foil, and after drying, a first positive electrode coating having a thickness T of 5 μm is formed; then, the second positive electrode slurry is coated on the first positive electrode coating, and after drying, a second positive electrode coating having a thickness of 47 μm is formed; then, in the same manner, the first positive electrode coating and the second positive electrode coating are stacked in sequence on the other side of the aluminum foil to obtain a double-sided electrode sheet; finally, after rolling, a positive electrode sheet to be used is obtained.

[0051] A preparation method for a lithium secondary battery, comprising:

[0052] 1) preparing a negative electrode sheet: dispersing a negative electrode active material (specifically artificial graphite) with conductive carbon black, styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) in deionized water at a mass ratio of 97:1:1:1, stirring evenly to obtain a negative electrode slurry, applying the negative electrode slurry to two opposite sides of a copper foil, drying and rolling to obtain a negative electrode sheet;

[0053] 2) Assembling the battery: stack the positive electrode sheet, separator and negative electrode sheet of Example 1 in order, wind them into a battery cell, package the battery cell with an aluminum-plastic film shell, then inject electrolyte into the battery shell, form and evacuate, and then package again, divide the capacity, and obtain a lithium-ion battery. The lithium-ion battery has a 2C charging system, a capacity of 4500mAh, and a charging cut-off voltage of 4.45V.

[0054] Other embodiments

[0055] According to the method for manufacturing the positive electrode sheet and the secondary battery described in Example 1, the positive electrode sheets and the secondary batteries of other examples were manufactured based on the parameters listed in Table 1. The calculation results of the above-defined parameter n are also summarized in Table 1.

[0056] Comparative Example 1

[0057] The difference between Comparative Example 1 and Example 1 is that the first positive electrode coating does not contain an electrochemically inactive inorganic filler.

[0058] Comparative Example 2

[0059] The difference between Comparative Example 2 and Example 1 is that the positive electrode plate does not contain the first positive electrode coating.

[0060] Table 1 Parameters of positive electrode sheets of various embodiments and comparative examples and test data of batteries

[0061]

[0062]

[0063] In order to highlight the beneficial effects of the technical solution of the present application, the following performance tests were also carried out on the above lithium-ion batteries, and the results are also summarized in Table 1 above.

[0064] (1) Internal resistance test

[0065] Each lithium-ion battery is placed in a room temperature environment (23-25°C), charged to 3.95V at a constant current of 0.2C, and then charged to a cut-off current of 0.01C at a constant voltage of 3.95V, and then the internal resistance of the battery cell is tested with an AC internal resistance meter of 1kHz. Among them, 10 batteries are taken for testing in each embodiment or comparative example, and the test average value is taken. Based on the internal resistance of the battery in comparative example 2 (about 25mΩ), the internal resistance increase rate of each other group of batteries is calculated. If the internal resistance increase rate is within 30%, it is considered to have passed the internal resistance test.

[0066] (2) Acupuncture test

[0067] Each lithium-ion battery is placed in a room temperature environment (23-25°C), charged to 4.45V at a constant current of 0.2C, and then charged to a cut-off current of 0.025C at a constant voltage of 4.45V. Then, the lithium-ion battery is fixed in a puncture test device, the ambient temperature is 23-25°C, the humidity is 40-60%, and a steel needle with a diameter of 3mm is used to pierce the center of the lithium-ion battery at a constant speed of 50mm / s. The steel needle stays in the battery for 10 minutes and then the needle is pulled out to observe whether the battery catches fire or explodes. Among them, 10 batteries are taken for testing in each embodiment or comparative example, and the percentage of batteries that do not catch fire or explode is recorded to obtain the puncture pass rate. Among them, when the puncture pass rate is 100%, it is considered to have passed the puncture test.

[0068] According to Table 1, when the composition of the positive electrode plate of the embodiment of the present application makes the particle stacking parameter n in the first positive electrode coating defined above be in the range of 4-7, and the average particle sizes of the first active material and the second active material are in the range of 0.6-1.2μm and 0.6-1.5μm, respectively, the lithium ion battery made using the positive electrode plate can pass the puncture test, which indicates that it has good safety performance; at the same time, compared with the battery of comparative example 2 without a safety coating, the internal resistance increase rate of the lithium ion battery of the embodiment of the present application is lower, within 30%, which is conducive to ensuring good cycle performance of the battery.

[0069] Among them, by comparing Example 1 with Comparative Example 2, it can be seen that under the protection of the first positive electrode coating, when the battery is pierced by a steel needle, the positive electrode collector has no direct contact with the negative electrode active material, which significantly reduces the risk of thermal runaway of the lithium ion battery. By comparing Example 1 with Comparative Example 1, it can be seen that when an inorganic filler with high thermal stability is added to the first positive electrode coating, the safety of the battery can be further improved.

[0070] By comparing Examples 1 and 2 with Comparative Examples 3-6, it can be seen that when the median particle size of the first positive electrode active material particles and the inorganic filler particles remains unchanged, when the thickness T of the first positive electrode coating makes the number of particle stacking layers n defined in this application less than 4 (Comparative Examples 5-6), the puncture pass rate of the battery decreases, which indicates that the first positive electrode coating cannot effectively play a safety protection function; when n exceeds 7 (such as Comparative Examples 3-4), compared with Comparative Example 2 without the first positive electrode coating, the internal resistance increase rate of the battery is too large, exceeding 30%. When the number of stacking layers N of the particles is greater than 4 and less than 7 (Examples 1-2), safety can be ensured while ensuring that the internal resistance of the battery does not increase too much.

[0071] By comparing Examples 1, 3-4 and Comparative Examples 7-9, it can be seen that the median particle size D of the first positive electrode active material lithium iron phosphate 1 v 50 and the thickness T of the first positive electrode coating is constant, the median particle size D of the inactive inorganic filler2 v 50 has no significant effect on the safety of the battery, but has a greater impact on the internal resistance of the battery. In Comparative Examples 7-8, the particle size of the inorganic filler is too small, resulting in the number of particle stacking layers n being greater than 7, and the increase rate of the battery internal resistance exceeds 30%; while the particle size of the inorganic filler in Comparative Example 9 is too large, and the corresponding battery internal resistance increase rate is too large. This is mainly because the inorganic filler is an insulator of electrons and ions, and its large particle size may cause the interruption of local electron and ion pathways in the first positive electrode coating, greatly increasing the internal resistance of the battery. When the median particle size of the inorganic filler is 0.8-1.5μm, a suitable number of stacking layers can be achieved, while controlling the increase in the battery internal resistance to a smaller range.

[0072] By comparing Example 1, Examples 5-6 and Comparative Examples 10-13, it can be seen that the thickness T of the first positive electrode coating and the median particle size D of the inorganic filler 2 v 50 unchanged, the particle size of the first positive electrode active material lithium iron phosphate has a significant impact on the safety performance and internal resistance of the battery. When the particle size of lithium iron phosphate is too small (such as comparative examples 10-11), the number of particle stacking layers n of the first positive electrode coating is too high, and the small particles are more densely stacked, which makes the internal resistance increase rate of the battery too large. When the particle size of lithium iron phosphate is too large (such as comparative examples 12-13), the internal resistance increase rate of the battery is very small, but the needle puncture pass rate is significantly reduced. This may be due to the fact that its particle size is too large, resulting in too few n, and the first positive electrode coating cannot play an effective protective role.

[0073] The above-described embodiments only express several exemplary implementations of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the present application. It should be noted that, for a person of ordinary skill in the art, several modifications and improvements may be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a first positive electrode coating and a second positive electrode coating sequentially stacked on at least one side of the positive electrode current collector; the first positive electrode coating comprises a first positive electrode active material and an inorganic filler without electrochemical activity, and the second positive electrode coating comprises a second positive electrode active material; the number of particle stacking layers n in the first positive electrode coating is defined to satisfy the following relationship: n=T×(M+1) / (M×D 1 v 50+D 2 v 50), and n is in the range of 4-7; Wherein, T is the thickness of the first positive electrode coating, T is in the range of 2-10 μm, in μm; M is the mass ratio of the first positive electrode active material to the inorganic filler, M is in the range of 1-5; D 1 v 50. D 2 v 50 are the particle sizes corresponding to the volume cumulative distribution percentages of the first positive electrode active material and the filler when they reach 50%, both in μm; wherein, D 1 v 50In the range of 0.6-1.2μm, the D 2 v 50 is in the range of 0.6-1.5μm.

2. The positive electrode sheet according to claim 1, characterized in that: The D 1 v 50 is in the range of 0.6-0.9μm.

3. The positive electrode sheet according to claim 1, characterized in that: The thermal decomposition temperature of the inorganic filler is greater than or equal to 300°C.

4. The positive electrode sheet according to claim 1, characterized in that: The first positive electrode active material includes one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, and lithium vanadium fluorophosphate; the second positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium vanadate, lithium titanate, lithium nickel manganese oxide, lithium nickel cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based materials.

5. The positive electrode sheet according to claim 1, characterized in that: The median particle size of the second positive electrode active material is in the range of 6 μm to 18 μm.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The first positive electrode coating layer further includes a first binder and a first conductive agent, and the second positive electrode coating layer further includes a second binder and a second conductive agent.

7. The positive electrode sheet according to claim 6, characterized in that: The mass proportion of the first binder in the first positive electrode coating is greater than the mass proportion of the second binder in the second positive electrode coating.

8. The positive electrode sheet according to claim 7, characterized in that: The mass proportion of the first binder in the first positive electrode coating is 5%-10%; the mass proportion of the first conductive agent in the first positive electrode coating is 1-3%.

9. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet as claimed in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Electrode, nonaqueous electrolyte battery, battery pack and vehicle

    CN107845768A

  • Positive pole piece, electrochemical device and electronic device comprising same

    CN113675366A